Hair-Growth-Promoting Effects of the Fish Collagen Peptide in Human Dermal Papilla Cells and C57BL/6 Mice Modulating Wnt/β-Catenin and BMP Signaling Pathways - Hwang, Su Bin; Park, Hyeon Ju; Lee, Bog-Hieu (International journal of molecular sciences, 2022)
Fish-derived collagen has recently emerged as an alternative collagen source with bioactive properties, including the enhancement of hair and skin health. It is also cost-effective and has high bioavailability, in addition to having fewer side-effects compared to collagen from porcine skin or bovine skin. Collagen peptides (CPs) extracted from the scales of Mozambique tilapia (Oreochromis mossambicus) reportedly promote hair and skin health. This study sought to evaluate the effects of CPs on hair growth using in vitro and in vivo models. CP significantly enhanced hair regrowth and the proliferation of human dermal papilla cells (hDPCs) in vitro. CP was orally administered to C57BL/6 mice for 6 weeks to confirm the hair-growth-promoting effects. The mice were divided into four groups: negative control (distilled water), positive control (1 mg/kg of finasteride), CP500 (500 mg/kg of CP), and CP1000 (1000 mg/kg of CP). CP treatment significantly enhanced the proliferation of hDPCs compared to 0.2 μM finasteride, in addition to enhancing hair regrowth. Particularly, CP1000 treatment achieved a hair-growth index similar to that of the PC. In H&E staining, the CP groups exhibited a high A/T ratio. Furthermore, CP increased the expression of hair growth factors (IGF-1, VEGF, krt27, Gprc5d, and Ki67) and decreased the growth inhibitory factor (TGF-β1). Furthermore, CP significantly upregulated the Wnt/β-catenin pathways and downregulated the BMP pathways. Therefore, these results indicate that CP could be used as food supplements and nutraceuticals for hair loss prevention as well as hair regrowth during alopecia.